The Impact of Ownership Structure on the Indicator of Financial Distress In Indonesian Companies - Annither, Annither; Johann, Michael Kester; Hidayat, Athalia Ariati; Farhana, Siti (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2020)
The increase in bankruptcy cases and delaying debt repayment by 16.43 percent during the year of 2015 to 2017 reinforced the importance of having good corporate governance to avoid this issue. This study aims to delve into the effect of ownership structures on the risk of financial distress in 421 companies (except financial institu-tions) in the period from 2012 to 2017. The types of ownership that are being exam-ined are Institutional Ownership, Insider Ownership, Government Ownership, and Foreign Ownership. This study uses OLS Driscoll-Kraay standard error panel data regression. The results of this study shows that Institutional Ownership has a positive relationship to financial distress which is caused by the tendency of Institutional in-vestors to conduct passive monitoring. Inversely, foreign ownership and government ownership have been proven to have a negative relationship with the risk of financial distress. This was caused by the capability of the foreign investors to do better- moni-toring activities and maintain the ultimate shareholder’s company in their home country. Furthermore, the presence of merah putih shares allows the government to have absolute voting power. This research intends to provide new business perspec-tives to companies, investors, regulators, creditors, and other stakeholders for eco-nomic decision- making purposes. Peningkatan perkara kepailitan dan penundaan kewajiban pembayaran utang sebe-sar 16.43 persen sepanjang tahun 2015-2017 menyadarkan kembali pentingnya tata kelola yang baik untuk menghindari hal tersebut. Penelitian ini mempelajari pengaruh struktur kepemilikan terhadap risiko kesulitan keuangan di perusahaan terhadap 421 perusahaan (kecuali lembaga keuangan) pada tahun 2012-2017. Jenis-jenis kepemilikan yang diteliti adalah kepemilikan institusional, kepemilikan manajerial, kepemilikan pemerintah, dan kepemilikan asing. Hal yang ditemui dari hasil penelitian ini yaitu dapat dibuktikan bahwa kepemilikan institusional memiliki hubungan positif terhadap risiko kesulitan keuangan yang disebabkan oleh kecender-ungan investor institusional untuk melakukan passive monitoring. Sebaliknya kepemilikan asing dan kepemilikan pemerintah terbukti memiliki hubungan negatif terhadap risiko kesulitan keuangan, dengan alasan kemampuan investor asing dalam melakukan kontrol dan menjaga reputasi perusahaan di negara asalnya. Sedangkan, pemerintah memiliki voting power yang bersifat mutlak dengan adanya saham merah putih. Penelitian ini bermaksud untuk memberikan perspektif baru kepada pihak-pihak yang berkepentingan untuk pengambilan keputusan ekonomi.